Do socioeconomic status, race and ethnicity modify the relationship between alcohol use and unintentional injury mortality? - Llamosas-Falcón, Laura; Zhu, Yachen; Kerr, William C.; Rehm, Jürgen; Probst, Charlotte (Injury prevention, 2025)
Background There is a knowledge gap regarding the potential roles that socioeconomic status (SES), race and ethnicity may play in the associations between alcohol use and injury risk. This study aimed to examine these factors as potential effect modifiers in the relationship between heavy episodic drinking (HED) and unintentional injury mortality. - Methods We used mortality-linked data from the 1997-2018 US National Health Interview Survey. We performed survey-weighted Cox proportional hazards models to evaluate the effect modification of education, income, race and ethnicity on the relationship between the frequency of HED and motor vehicle and other unintentional injuries mortality. - Results 559 442 participants were included, with 772 motor vehicle fatalities and 2003 other unintentional injury deaths. Our cohort study found no significant interaction effect between SES, race and ethnicity, and HED on motor vehicle fatalities. For other unintentional injury mortality, we identified a significant interaction effect between low education and HED once or more per month (HR 2.75, 95% CI 1.38 to 5.49). Similarly, we found a significant interaction effect between low income and HED once or more per month (HR 1.84, 95% CI 1.02 to 3.34). Finally, both Black and Hispanic participants exhibited a higher risk of other fatal unintentional injuries at varying frequencies of HED compared with White participants. - Conclusions Our results emphasise the importance of considering SES, race and ethnicity in understanding the complex interplay between alcohol consumption and unintentional injury mortality. Understanding subgroup-specific dynamics is crucial for formulating targeted interventions to address disparities and enhance public health outcomes.
Gesehen am 05.11.2025